Description of Macronutrients, Natrium Intake, Nutritional Status, Smoking Habit, and Physical Activity in Hypertension Sufferers Aged 40-60 Years in Pabean Village, Sedati District, Sidoarjo Regency - Farrari, Delia Kintan; Ruhana, Amalia (Jurnal Ilmiah Wahana Pendidikan, 2023)
Health problems characterized by an increase in systolic and diastolic blood pressure, where ≥140 mmHg for systolic blood pressure and ≥ 90 mmHg for diastolic blood pressure after repeated examinations, are called hypertension. The number of people with hypertension at the Sedati Health Center according to the results of the preliminary study has increased to 28,624 patients in 2021. Most of the people with hypertension are residents of Pabean Village, as many as 5,675 people. The implementation of this research aims to analyze individuals who experience hypertension in the age range of 40-60 years in Pabean Village, Sedati District, Sidoarjo Regency in terms of physical activity, smoking behavior, nutritional status, sodium levels and macronutrient intake which includes fat, protein and carbohydrates. The implementation of this research is descriptive-quantitative type by implementing a cross-sectional design model. Furthermore, the sample selection method applied a purposive sampling method with the Slovin equation at a 10% significance level and 100 respondents were obtained as samples. Furthermore, the method used in collecting data is a questionnaire, where data related to intake of macronutrients and sodium is obtained from the results of the SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire), the results of measuring weight and height to obtain data on nutritional status, questionnaires smoking habits, and the Baecke Questionnaire to obtain physical activity data. the data analysis model uses univariate analysis. Based on the test results, 73% of respondents had a deficit level of carbohydrate intake, 60% of respondents had a deficit level of protein intake, 56% of respondents had an excess level of fat intake, 81% of respondents had an excess level sodium intake, 51% of respondents had an obesity nutritional status, 21% of respondents were included in the category moderate smoking habits, and respondents who fall into the heavy physical activity category is 62%.